Completeness, Accuracy and Presentation of Information on Interactions Between Prescription Drugs and Alternative Medicines: An Internet Review - Scarton, Lou Ann (2013)
BACKGROUND: As the use of the Internet continues to increase across all age groups and education levels, with usage in the US around 78%, consumers are increasingly turning to the Internet for health related information. OBJECTIVE: To assess the completeness, accuracy, and consumer friendliness of information on the Internet pertaining to drug-Complementary and Alternative Medicine (CAM) interactions with cardiac drugs. METHODS: A review of online information was performed across three search engines and ten drug-CAM pairs. RESULTS: Overall, the quality of the drug-CAM interaction information available online to consumers is fairly poor. Only one site contained an interaction checker that provided interaction information for all ten pairs, but with an accuracy rate of 50%. Reading levels ranged from 10.5–23.5, with a mean of 16.7. A value greater than 22 indicates a graduate level reading skill. CONCLUSION: Web site developers should be cautious in presenting drug-CAM interaction information unless it is comprehensive and regularly maintained. Consumers should also know how to evaluate sites before trusting the content where the consequences are potentially severe.